APLIKASI DOSIS KOMPOS TITHONIA DAN KONSENTRASI PGPR FLORAONE® TERHADAP PERFORMA PERTUMBUHAN DAN HASIL TERUNG - Resti Hayati; Elara Resigia; Warnita (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[APPLICATION OF TITHONIA COMPOST DOSAGE AND PGPR FLORAONE® CONCENTRATION ON THE GROWTH PERFORMANCE AND YIELD OF EGGPLANT].  Eggplant is an important horticultural crop with high nutritional value, essential for maintaining health. Increasing eggplant production can be achieved through the use of superior varieties and optimized cultivation techniques. However, much of Indonesia's agricultural land consists of marginal soils, such as Ultisol, which pose challenges to cultivation. These challenges can be mitigated by incorporating organic materials, such as Tithonia compost, and utilizing Plant Growth-Promoting Rhizobacteria (PGPR).This study aimed to evaluate the interaction effects of different doses of Tithonia compost and concentrations of PGPR FloraOne® on the growth and yield of eggplant. The experiment was conducted from February to May 2023, using a completely randomized design (CRD) with two factors and three replications. Data were analyzed using analysis of variance (ANOVA) with an F-test at a 5% significance level, followed by HSD for mean separation. The results indicated that the combination of Tithonia compost at a dose of 15 tons/ha and PGPR concentration of 45 mL/L yielded the earliest flowering time. Tithonia compost significantly influenced plant height, leaf number, flowering time, number of flowers, fruit length, fruit diameter, fruit number, and fruit weight per plant. Meanwhile, PGPR application significantly affected leaf number, flowering time, and fruit length. These findings highlight the potential of integrating Tithonia compost and PGPR to enhance eggplant growth and productivity, particularly on marginal soils.